(untitled) (Tanzania Medical Journal, 2016)
Presentation of abdominal migraine poses a challenge in diagnosis. We present a case of a 5-year old boy with chronic abdominal pain of which different modalities of treatment including laparotomy were given without improvement until anti-migraine drug was initiated. More research is needed to better understand and manage abdominal migraine.